Conceptualising organisational learning system model and innovativeness / Thilageswary Arumugam and Khairuddin Idris - Arumugam, Thilageswary; Idris, Khairuddin (2014)
The connection between organisational learning, organizational innovativeness and performance is very profound in the literature. Performance especially is examined from the very comprehensive perspective, including dimension like financial performance, sales, profitability, service quality etc. Given that, this research focuses on collective learning aspect and the connection between organizational innovativeness and performance. Organizational Learning Systems Model (OLSM) focuses on organizational learning as a social system and how it learns to survive in the environment. Emphasis on organization learning based like Parsons (1968) general theory of social action has linked performance and learning element (Gorelick, 2005) in order to measure organizational performance. The Organizational Learning Systems Model (OLSM) grounded from the Parsonian social system perspective which is active in nature help identifies the importance of functioning and learning process of modification. Organizational learning here is drawn from behavioural dimensions; knowledge acquisition, information distribution, data interpretation, and organizational memory based on Huber’s (1991) work (Jiménez, 2008). Evidence has shown that organizational performance increases when learning occurs in an organization. Organisational innovativeness has shown the relationship with learning. This study seeks to assess the relationship between organizational learning systems model, organisational innovativeness that leads to positive output for organization. This work sought to bestow to the empirical research needs in the future.